OTA-based electronically adjustable floating positive/negative resistor - Petchmaneelumka, Wandee; Kamsri, Thawatchai; Wangwiwatthana, Chaleampan; Riewruja, Vanchai (My University, 2008)
This paper presents a method to realize an operational transconductance amplifier (OTA) based adjustable floating resistor. The magnitude of the resulting resistance can be electrically varied by changing the external bias currents of OTAs. The proposed resistor is based on an active network termed "dual-output voltage-to-current (DO-V/I) converter", which is the OTA-based voltage-to-current converter with electronically variable property. The realization method provides both a positive and a negative resistance using the same scheme. The proposed design is attractive in the terms of simple configuration and low cost. Experimental results showing the circuit performance based on the use of the commercially available OTAs are included. © 2008 SICE.
Keywords: DO-V/I; Floating resistor; OTA; Resulting resistance